The Implementation Of Clustering Technique To Improve Students’ Writing Skill In Descriptive Text Of The Eighth Graders Of MTs Darul Ulum Purwoasri Sukosewu Bojonegoro In The Academic Year Of 2012/2013. - M. Ali Ghufron (Jurnal Pendidikan Edutama, 2014)
The Implementation of Clustering Technique to Improve Students’ Writing Skill in Descriptive Text of The Eighth Graders of MTs Darul Ulum Purwoasri Sukosewu Bojonegoro in the Academic Year Of 2012/2013. This research is aimed at finding out whether the implementation of clustering technique can improve students’ writing skill in descriptive text. This research is categorized as Classroom Action Research (CAR) in which there are two cycles in this research. The population of this research was the eighth graders of MTs Darul Ulum in the Academic Year of 2012/2013 which consists of 32 students. The result shows that the implementation of clustering technique can improve the students’ writing skill in descriptive text significantly of the eight graders of MTs Darul Ulum Purwoasri Sukosewu Bojonegoro in the Academic year of 2012/2013.Keywords: Clustering Technique, Writing Skill, Descriptive Text